Numerical simulations of migration and coalescence behavior of microvoids driven by diffusion and electric field in solder interconnects. (April 2017) - Liang, S.B.; Ke, C.B.; Ma, W.J.; Zhou, M.B.; Zhang, X.P.
Abstract: A diffuse interface model is developed to simulate the effect of electric field on the morphological evolution and migration behavior of the microvoid in the solder interconnect consisting of the Sn based solder and Cu substrate (i.e., Sn/Cu system). The model takes into account the coupled effect of surface diffusion and electric field, and the validity of the model is confirmed by good agreement between the simulation and theoretical predictions in terms of evolution behavior of the noncircular microvoid driven by surface energy. The results show that the coalescence of microvoids driven only by surface energy occurs when the microvoids contact each other. The evolution and migration of the microvoid under electric field are governed by the magnitude of electric field and the initial size of the microvoid. The microvoid migrates at a constant velocity under a weak electric field, while the strong electric field results in the shape change of the microvoid from circular to narrow crack-like. In addition, the migration velocity of the microvoid increases linearly with the voltage and is inversely proportional to the size of the microvoid; a small microvoid can catch up with a large one, and finally they merge to form a larger microvoid, which may promote the open circuit failure near the solder/Cu interface in solder interconnects. Highlights: The electric field is coupled to phase field model. Effect of surface diffusion and electric field on microvoid migration is clarified. Small microvoid migrates faster and merges with large one under electric field. Shape of large micorvoids can more easily become unstable under electric field. Migration kinetics of microvoid under electric field is characterized.